Water Management in the Watershed of the Phalgu River of Central Bihar - Sinha, B.P.; Dubey, B.P.; Lal, J.P.; kumar, Sunil (Journal of Soil and Water Conservation, 2022)
A brief account of the characteristics of the Phalgu watershed has been provided to indicate the extent and severity of water management problems in the Phalgu Watershed. Three major identified tasks are (1) control of run off water on land surface and river flow (2) efficient and judicious exploitation and use of ground water and (3) recharge of ground water. All these aspects have been discussed in brief in the present paper for efficient and effective management of the watershed of Phalgu river.